2022
DOI: 10.3390/pr10050856
|View full text |Cite
|
Sign up to set email alerts
|

Sorbent Properties of Orange Peel-Based Biochar for Different Pollutants in Water

Abstract: Efficient and reasonable utilization of waste biomass resources can not only avoid serious waste of material resources, but also solve the problem of environmental pollution. Therefore, the development of efficient and environmentally friendly waste biomass carbonization technology has important practical significance. Here, the activated carbon from orange peel (OAC) is prepared by potassium hydroxide (KOH) activation combined with high-temperature carbonization. The adsorption effects of OAC on three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The diffractogram of Ni/BC exhibits specific peaks at 2θ of 27.5°, 44.8 and 52.3°, associated with 220, 111 and 200 reflections of a-FCC of single nickel nanoparticles (Ni), referring to JCPDS: 03-1051 [ 15 , 16 , 17 ]. In addition, a small broad peak ranging from 20°–30° is also identified similar to the broad peak in BC, implying the presence of a structure of aromatic layers (graphite 002) [ 18 , 19 ]. The broad peak expresses a small dimension of crystallites perpendicular to the aromatic layers as the characteristic of biochar structure.…”
Section: Resultsmentioning
confidence: 99%
“…The diffractogram of Ni/BC exhibits specific peaks at 2θ of 27.5°, 44.8 and 52.3°, associated with 220, 111 and 200 reflections of a-FCC of single nickel nanoparticles (Ni), referring to JCPDS: 03-1051 [ 15 , 16 , 17 ]. In addition, a small broad peak ranging from 20°–30° is also identified similar to the broad peak in BC, implying the presence of a structure of aromatic layers (graphite 002) [ 18 , 19 ]. The broad peak expresses a small dimension of crystallites perpendicular to the aromatic layers as the characteristic of biochar structure.…”
Section: Resultsmentioning
confidence: 99%
“…The specific surface area, total pore volume and pore diameter (nm) are summarized in Table 1. Comparing the C1 and C2 adsorbents, it can be observed that at high temperatures, the organic matter in the orange peel decomposes, increasing the specific surface area [34]. After the heat treatment, in addition to the specific surface, the total volume of the pores also increases.…”
Section: Surface Area Determinationmentioning
confidence: 99%
“…Do et al [30] used NaOH modifed Moringa oleifera leaf to prepare activated biochar to remove MB from aqueous solution. Te study showed that the maximum adsorption capacity for MB was 136.99 mg/ g when the pH was 7 and the adsorbent dosage was 1.67 g/ L. Activated biochar was mainly prepared by chemical activation and physical activation methods, of which, ZnCl 2 , KOH, and NaOH are commonly used as activators to produce activated biochar with high specifc surface area [31][32][33]. NaOH and KOH are commonly used for lignocellulosic biomass chemical activation [34].…”
Section: Introductionmentioning
confidence: 99%